Concurrent growth, structural and photocatalytic properties of hybridized C, N co-doped TiO2 mixed phase over g-C3N4 nanostructured. (1st January 2018) - Mohamed, Mohamad Azuwa; Jaafar, Juhana; M. Zain, M.F.; Minggu, Lorna Jeffery; Kassim, Mohammad B.; Salehmin, Mohd Nur Ikhmal; Rosmi, Mohamad Saufi; W. Salleh, W.N.; Othman, Mohd Hafiz Dzarfan
Abstract: A concurrent and facile sol-gel assisted low temperature calcination approach to homogeneous growth of TiO2 mixed phase nanoparticles over g-C3 N4 for designing visible-light-driven photocatalyst is demonstrated in this study. The structural and morphological studies revealed a well-interconnected g-C3 N4 /TiO2 mixed phase heterojunction photocatalyst was achieved through a sol-gel process and calcination at 400 °C. The well-interconnected g-C3 N4 /TiO2 mixed phase heterojunction photocatalyst has strong visible light absorption capability due to the presence of an in-situ nitrogen and carbon dopants. The noticeably increased in the visible-light-photocatalytic activity performance is ascertained mainly due to the improvement of electron-hole separation and charge carrier migration. Graphical abstract: